2019
DOI: 10.1002/anie.201813910
|View full text |Cite
|
Sign up to set email alerts
|

Alkene Transfer Hydrogenation with Alkaline‐Earth Metal Catalysts

Abstract: The alkene transfer hydrogenation (TH) of a variety of alkenes has been achieved with simple AeN′′2 catalysts [Ae=Ca, Sr, Ba; N′′=N(SiMe3)2] using 1,4‐cyclohexadiene (1,4‐CHD) as a H source. Reaction of 1,4‐CHD with AeN′′2 gave benzene, N′′H, and the metal hydride species N′′AeH (or aggregates thereof), which is a catalyst for alkene hydrogenation. BaN′′2 is by far the most active catalyst. Hydrogenation of activated C=C bonds (e.g. styrene) proceeded at room temperature without polymer formation. Unactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 46 publications
1
67
0
Order By: Relevance
“…20,23 With these observations in mind, our attention was drawn to Harder's recent demonstration of the potency of such hydride reagents toward the transfer hydrogenation of C-C multiple bonds. 24 This chemistry utilised 1,4-cyclohexadiene (1, as the source of dihydrogen during which the cyclic diene is aromatised to benzene. Density functional theory (DFT) calculations demonstrated that this transformation ensues through a sequence of 1,4-CHD deprotonation and hydride elimination from the resultant cyclohexadienyl intermediate.…”
mentioning
confidence: 99%
“…20,23 With these observations in mind, our attention was drawn to Harder's recent demonstration of the potency of such hydride reagents toward the transfer hydrogenation of C-C multiple bonds. 24 This chemistry utilised 1,4-cyclohexadiene (1, as the source of dihydrogen during which the cyclic diene is aromatised to benzene. Density functional theory (DFT) calculations demonstrated that this transformation ensues through a sequence of 1,4-CHD deprotonation and hydride elimination from the resultant cyclohexadienyl intermediate.…”
mentioning
confidence: 99%
“…3) may be converted to n-alkyl species by their reaction with unactivated alkenes. 12,15,16,55,56 In this joint synthetic and computational study, we demonstrate that terminal alkenes and unhindered alkynes also react directly with compound 4 and that subsequent silane metathesis of the resultant organomagnesium species provides a basis for the hydrosilylation of C-C unsaturated substrates.…”
mentioning
confidence: 87%
“…Reminiscent of the reactivity of the calcium hydride (3), 14 compound 4 was found to be completely unreactive towards the internal alkenes, 2,3-dimethyl-2-butene, cyclopentene and cyclohexene but to react smoothly, albeit slowly, with both the strained bicyclic alkene, norbornene (3 days at 80 C) and the internal alkyne, diphenylacetylene (6 days at 80 C), to provide the magnesium norbornyl (15) and (E)-(1,2-diphenylvinyl) (16) derivatives. Although monitoring of the reaction with norbornene revealed tentative evidence that the production of 15 occurs via the formation of a dinuclear hydridonorbornyldimagnesium intermediate (Fig.…”
Section: Stoichiometric Reactions Of Compound 4 With Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these distinct clusters was rationalized via a self‐assembly process that is controlled by the (Me 3 Si) 2 N anion and neutral ligands. It is thought that a variety of similar clusters are the catalytically active species in hydrogenation of alkenes and imines using H 2 and simple alkaline earth metal amide catalysts like Ae[N(SiMe 3 ) 2 ] 2 (Ae = Mg, Ca, Sr, Ba) . Although one example for self‐assembly of a larger magnesium hydride cluster stabilized by a neutral ligand has been mentioned ( IV ), we wondered whether cluster formation may be controlled by variation of the neutral ligand.…”
Section: Introductionmentioning
confidence: 99%